Peran tik dalam menciptakan pembelajaran adaptif dan berkelanjutan di era society 5.0 - Novitasari, Rizki Cahya; Saputri, Juliana; Sumarno, Sumarno (Jurnal Madako Education, 2024)
Due to its enormous influence on human activities, ICT has developed into a vital instrument in various scientific disciplines. This is due to the fact that ICT has radically changed managerial and operational practices, as well as practices in the transport, health, education and research industries. Learning media is an instrument that disseminates educational messages and data. Learning materials that are well structured and created really help students' acquisition and understanding of the subject matter. The development of learning media is accelerated by the very rapid progress of information and communication technology. ICT is used as a vital educational tool and media. ICT education can improve the quality of human resources and is very important for the progress of society in the 5.0 era. Advances in ICT in the social era. The goal of 5.0 is to bring society's economy closer to today's society. 1. In addition to basic reading, society will need other skills in the future, including problem solving, critical thinking, reasoning, discovery, communication, and teamwork, as we enter the society 5.0 period. Currently, there are many popular sources for learning technology information, including the internet, intranet, cell phones, CDR/Flash Disks, and others. The learning model must be modified so that it is constantly updated in line with increasingly rapid changes in development and brought about by technological advances.